KONSEP PENDIDIKAN ANAK USIA DINI DALAM PERSPEKTIF PENDIDIKAN ISLAM - Nini Aryani (POTENSIA: Jurnal Kependidikan Islam, 2015)
Islamic education is a process that leads people to the good life and the uplifting of humanity in accordance with the basic capabilities (nature) and the his teaching ability (external influences). True education is that provides the opportunity for openness to influences from the outside world and the development of the students themselves. Thus the nature then it is given the right to form the individual child and at the same time external factors will educate and direct the child's basic abilities. Therefore, education is operationally contains two aspects, namely maintaining or improving and growing aspect or fostering. The basic concepts of early childhood education emphasizes to optimize child development and meet the child's characteristics that are unique individuals, who have experience and knowledge are different, it is necessary to do business by providing stimuli, impulses and support to children. In connection with it, the concept of early childhood education can include the formation of attitudes and the development of basic skills entirety useful to realize a perfect man who is able to stand alone, responsible and have a stock to enter further education it is also consistent with the view in the Islamic education.